Scope of Social Work Practice for Families of Children with Down Syndrome - Khan, Bilal Ahmad; Zargar, Wakar Amin; Najar, Shabir Ahmad (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
ocial work practice takes place at micro, mezzo, and macro levels between persons with disabilities in families and other social institutions, such as schools, health systems, and welfare systems. Drawing from multidisciplinary theoretical sources, the article brings together social work and family therapy to develop a possible social work intervention for families of children with Down syndrome. The primary purpose of these interventions is to aid clients in alleviating problems and improving their well being. Social workers must think creatively about interventions that may help the individuals, couples, families, and groups or communities they serve. This research is using the literature study method. The results confirm that numerous concerns have to be addressed faced by children with Down syndrome. Toward various issues and challenges faced by people with Down syndrome and their families, social workers have the professional responsibility to provide services and intervention to increase the children with Down syndrome’s social functioning and overall well-being of parents.